Pengaruh Self-Efficacy dan Adversity Quotient terhadap Academic Procrastination Mahasiswa di Universitas Muhammadiyah Sidoarjo - Galuh Syahrial Ibrahim; Dwi Nastiti (Universitas Darul Ulum, 2026)
Academic procrastination is a common problem among university students and can hinder academic achievement. Low self-efficacy and weak ability to face difficulties are assumed to contribute to this behavior. This study aims to examine the influence of self-efficacy and adversity quotient on academic procrastination among students of Universitas Muhammadiyah Sidoarjo. This study used a quantitative correlational design. The population consisted of 8,103 active students, with a sample of 343 students selected using incidental sampling. Data were collected using self- efficacy, adversity quotient, and academic procrastination scales. Data were analyzed using multiple linear regression. The results show that self-efficacy and adversity quotient simultaneously influence academic procrastination, and partially both variables have a negative influence. In conclusion, higher self-efficacy and stronger adversity quotient play an important role in reducing academic procrastination among students.